E-MONEY : AN ISLAMIC PERSPECTIVE - 'Aini, Tsabitah Qurratun; Shofia, Lira Risti; Sulistia, Sulistia; Nabilah, Hafidah; Anshari, Rahman (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to find out and explain the definition, history and law in Islam towards e-money as a means of payment, as well as the positive and negative impacts of using e-money itself. The research method used is a qualitative method. The research approach used is the study literature review approach, which is a method that identifies and evaluates research results and ideas that have been produced by researchers and practitioners. The literature method comes from various sources, such as books and journal articles. The results of this study know that the law of using e-money in an Islamic perspective as a means of payment is halal or permissible.